2015
DOI: 10.3390/ijerph120605712
|View full text |Cite
|
Sign up to set email alerts
|

Road-Traffic Noise: Annoyance, Risk Perception, and Noise Sensitivity in the Finnish Adult Population

Abstract: Exposure to road-traffic noise commonly engenders annoyance, the extent of which is determined by factors not fully understood. Our aim was to estimate the prevalence and determinants of road-traffic noise annoyance and noise sensitivity in the Finnish adult population, while comparing the perceptions of road-traffic noise to exhausts as environmental health problems. Using a questionnaire that yielded responses from 1112 randomly selected adult Finnish respondents, we estimated road-traffic noise- and exhaust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
1
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(46 citation statements)
references
References 48 publications
3
32
1
8
Order By: Relevance
“…Observational and experimental studies suggested that noise can increase annoyance levels (2,3), undermine sleep quality and cause daytime drowsiness (4), worsen patient outcomes and staff performance in hospitals (5), and impair cognitive performance in school children (6,7). It may induce these physiological and psychosocial responses, and ultimately extra-auditory system disorders, by stimulating the hypothalamus-pituitary-endocrine system and by altering blood dynamics and hormone levels (8).…”
Section: Introductionmentioning
confidence: 99%
“…Observational and experimental studies suggested that noise can increase annoyance levels (2,3), undermine sleep quality and cause daytime drowsiness (4), worsen patient outcomes and staff performance in hospitals (5), and impair cognitive performance in school children (6,7). It may induce these physiological and psychosocial responses, and ultimately extra-auditory system disorders, by stimulating the hypothalamus-pituitary-endocrine system and by altering blood dynamics and hormone levels (8).…”
Section: Introductionmentioning
confidence: 99%
“…The comparison of people's subjective opinions and the data collected on actual noise pollution has shown that in many areas the subjectively experienced and the measured noise levels overlap. This was typical in the case of heavy road traffic, as adults are highly irritated by traffic noise and consider it a significant health risk (Okokon, et al, 2015).…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, passing mood and sensitivity can also affect people's perception of noise (Waye & Öhrström, 2002). As Okokon et al (2015) have stated, traffic noise is annoying for adults, but the same level of noise near places such as the lake mentioned above does not produce similar levels of irritation, and so is not marked on the map as a noisy place.…”
Section: Discussionmentioning
confidence: 99%
“…Many residents exposed to outdoor traffic noise consider it unacceptable for sound sleep and amenity [3]. Road-traffic noise is a widespread environmental nuisance which affects people in their residential dwellings and workplaces [4]. Residential exposure to noise pollution, particularly road traffic noise, is an important issue because people spend 10-15 hours per day at home than other places such as office and school [5].…”
Section: Introductionmentioning
confidence: 99%